Rare complication of permanent pacemaker: protrusion of the battery connected to the pacemaker pocket infection - Ercan, Süleyman; Sucu, Murat; Yavuz, Fethi; Bosnak, Vuslat; Davutoğlu, Vedat (European Journal of Therapeutics, 2023)
Pacemaker pocket infection will recently increasingly be seen as a problem related to expanding range of indications of the permanent pacemaker, cardiac resynchronization therapy, implantable cardioverter defibrillator (ICD). Seventy-four-year-old male patient with ICD implanted in 2008 due to ischemic cardiomyopathy, who had the pacemaker battery protruding from the skin after pacemaker pocket infection. After 4 weeks of antibiotic therapy, all pacemaker equipment removed by surgery. Pacemaker pocket infection developed more frequently in the presence of risk factors, needs long-term use of antibiotics, and surgical treatment as complicated.